PERCEPTION OF ISLAMIC CULTURAL POLICY IN BURUNDI - Simon Ntamwana (Sanata Dharma University, 2022)
The purpose of this paper was to examine the perception of Islamic religious cultural policy in Burundi. The research focused on the perception of culture-shaping policies based on Islam by Burundians. The discussion of the views of informants was based on Syed Muhammad Naquib Al-Attas’ approach to Islam and secularism. Primary data were collected from 40 university Christian students through questionnaires. The subjects included undergraduates and postgraduates studying in the Department of Languages and Social Sciences at Ecole Normale Supérieure. Secondary data were obtained from books, policy documents, and internet resources. It was found out that Christians in Burundi do not desire the Islamic cultural policy that is applied in Islamic States due mostly to its relation to radicalism and terrorism and the rejection of Christianism as a divinely revealed religion. Additionally, it was found out that some habits and practices among Muslims such as marrying many women, growing beard, and the secret bathing of the bodies of dead Muslims generate a negative perception of Islam. However, some values and arts that are practiced among Burundi Muslims such as women veiling, fashion, cookery, knitting, and embroidery are highly appreciated.